THE ROLE OF DOMESTIC INVESTMENT (DI) AND BUSINESS, MICRO, SMALL AND MEDIUM (MSMEs) IN INVESTMENT IN INDONESIA - Graceya Iranita Tarigan; widia; Alivia Putri Aina; Chyntia; Nathaniela Putri Arumdhani; Luna Diana Puteri (Zhata Institut, 2024)
One indicator of a country's national development is its economic growth. Economic development is an indicator to find out how successful a country's economic development is and also as a determinant of development policies that will be formed next. Economic growth and development aim to increase job opportunities for the community, which must involve all levels of society in its implementation. One component that plays an important role in Indonesia's economic growth is Micro, Small and Medium Enterprises (UMKM) and also Domestic Investment (PMDN). UMKM plays a role in the absorption of labor so that they also contribute to national income. However, the economic growth of a country can also be helped by investment. This research is a normative legal research using secondary data, as well as a statutory approach which is then compiled qualitatively. The conclusion of this study shows that the role of UMKM in the development of investment in Indonesia is in terms of expanding the provision of employment, making a significant contribution to the development of a country, distributing income increases and increasing the competitiveness and resilience of the national economy. Meanwhile, PMDN plays a role in financing which is important for developing regions and is able to make a sizable contribution to development and plays a role in increasing economic growth through a conducive investment climate in Indonesia.